USING A SOFTWARE PACKAGE FOR PREDICTING THE STATE OF THE INTERDENTAL GINGIVAL PAPILLA IN PATIENTS WITH GENERALIZED PERIODONTITIS AFTER RESTORATION OF THE CONTACT SURFACES OF THE POSTERIOR TEETH - Kopchak, O.V.; Obolonska, H.O.; Kulish, A.S.; Azarov, O.V.; Іakovets O.V.; Shnaider, K.S. (World of Medicine and Biology, 2024)
The study was devoted to the analysis the possibilities of a software product to determine the probability of preserving or restoring interdental gingival papillae depending on the parameters of the elements of the interdental triangle during the direct restoration of caries-affected contact surfaces of the posterior teeth in patients with generalised periodontitis of the initial and initial-I degree of severity. The clinical trial involved 150 patients aged 18 to 45 years. To predict the likelihood of preserving or restoring interdental papillae during the restoration of the contact surfaces of the posterior teeth in patients with generalised periodontitis, the Papillary Expert software product was developed and clinically tested. The developed software provided a high level of accuracy in predicting the preservation or restoration of interdental gingival papillae after restoration of the contact surfaces of posterior teeth in patients with generalized periodontitis, thereby aiding in selecting the most effective treatment strategies.